PENGARUH SOCIAL MEDIA MARKETING, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN PRODUK SCARLETT WHITENING PADA GENERASI Z DI KOTA PEKANBARU - ,Tengku Firli Musfar, Armeinita Octavia Siregar ,Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to prove the Influence of Social Media Marketing, Price, and Product Quality on Purchasing Decisions and Consumer Satisfaction of Scarlett whitening Products in Generation Z di Pekanbaru City. The population in this study is generation Z respondents who live in Pekanbaru and have purchased and used Scarlett whitening products. The sampling technique is carried out with a nonprobability sampling technique, namely purposive sampling where respondents are determined by certain criteria. The sample in this study was teenagers aged 17 to 26 years who had bought and used Scarlett whitening products who lived in the city of Pekanbaru. The data used in this study are primary data. The source of this research is by distributing questionnaires to respondents. To find factors Influence of Social Media Marketing, Price, and Product Quality on Purchasing Decisions and Consumer Satisfaction Scarlett whitening Products in Generation Z di Pekanbaru City used multiple linear regression tests and Path analysis. The results of the analysis showed that there was an influence of independent variables on independent variables and it was found that the purchasing decision variables successfully mediated independent variables. Keywords: Social Media Marketing, Price, Product Quality, Purchasing Decisions, Consumer Satisfaction